Unveiling The Dream: The New Frontiers of Dream Technology and Radical Rest - Imani, Mia; Finna, Saelyx (Intermédialités / Intermediality, 2023)
This article situates the meeting points of dream tech and the radical rest movement, centering on Black creative and community practices to contextualize the emergence of dream tech in academic research labs, tech startups, consumer markets, and artistic incubations. The article describes the rise of the Radical Rest movement, led by Black activists and artists, in response to the need to reclaim sleep and dreams from colonial agendas and capitalist systems of oppression. This movement has developed parallel to the rapid growth of sleep technology, offering new products for sleep-deprived consumers of the global North. The next frontier of this new multibillion-dollar industry is dream neurotech—technology that directly interfaces with the dreaming mind. The article introduces dream tech by unearthing a largely forgotten dream that shaped the trajectory of modern Western science, a trajectory that is contrasted with views about consciousness in sleep espoused by classical Indian philosophers. With this historical and global context for understanding how sleep and dreams are measured and quantified, the article then historicizes racial sleep inequities in the U.S. to frame how systematic oppression continues to have adverse effects on the sleep health of Black Americans. The article examines the aims of commercial dream tech, discerning agendas and assumptions that reverberate with the Cartesian dualism underlying Western scientific views of dreams, selfhood, and consciousness. These views will be complicated by the practices and values of Black activists and artists in the contemporary Radical Rest movement. Their work uplifts physical and emotional rest as a powerful site for healing trauma and resisting the oppressive vectors of white supremacy and capitalism.